Metformin Facilitates Osteoblastic Differentiation and M2 Macrophage Polarization by PI3K/AKT/mTOR Pathway in Human Umbilical Cord Mesenchymal Stem Cells. (18th June 2022) - Shen, Min; Yu, Huihui; Jin, Yunfeng; Mo, Jiahang; Sui, Jingni; Qian, Xiaohan; Chen, Tong
Abstract : Mesenchymal stem cells (MSCs) are the most promising multipotent stem cells that can differentiate into osteoblasts, chondrocytes, and adipocytes. This cellular flexibility contributes to widespread clinical use of MSCs in tissue repair and regeneration. The immune system is a key player in regulating bone remodeling. In recent years, the association between the immune system and bone metabolism has become an increasing focus of interest. Metformin, a glucose-lowering drug, exerts powerful impact on metabolic signaling. However, whether metformin can modulate bone metabolism or whether metformin can influence immune milieu by regulation of macrophages has not been thoroughly elucidated. Herein, we specifically explored the complex interactions between macrophages and human umbilical cord mesenchymal stem cells (UC-MSCs) in the context of metformin. Our research demonstrated that metformin not only stimulated osteogenesis of UC-MSCs but also influenced the immune system via promoting M2 but reducing M1 macrophages. Mechanically, we found that metformin-treated M2 macrophages possessed more potent osteoinductive capacity in our coculture system. Molecularly, these metformin-stimulated M2 macrophages facilitated osteogenesis via activating the PI3K/AKT/mTOR pathway. As demonstrated by using PI3K-specific inhibitor LY294002, we found that the pathway inhibitor partly reversed osteoinductive activity which was activated by coculture of metformin-treated M2 macrophages. Overall, our novel research illuminated the cooperative and synergistic effects of metformin and M2 macrophages on the dynamic balance of bone metabolism.